High-Pressure Processing (HPP) Energy Efficiency and Scalability Challenges in Ultra-Processed Meat: A Review - Shaka Kusuma Nurjati; Muhammad Adam Purnawan; Rizma Stevviani (Journal of Clean Technology, 2025)
The global expansion of ultra-processed meat products (e.g., sausages, nuggets) faces dual challenges: microbiological safety risks from conventional thermal processing and rising consumer demand for clean-label, nutritious options. High-Pressure Processing (HPP) emerges as a promising non-thermal technology to address these concerns by inactivating pathogens while preserving sensory and nutritional quality. However, its industrial adoption is hindered by significant energy efficiency and scalability constraints. This systematic literature review synthesizes recent research to critically analyze these barriers. Methodologically, we conducted a Systematic Literature Review (SLR) using databases such as Scopus, ScienceDirect, Web of Science, and PubMed, focusing on studies related to High-Pressure Processing (HPP) applications in ultra-processed meats. Our analysis reveals that HPP consumes 2.5–3.2 kWh/kg up to 26× more energy than thermal pasteurization primarily due to hydraulic system demands and adiabatic heat dissipation during batch cycling. Scalability limitations stem from batch-based processing (3–7 min/cycle), vessel size constraints (<500 L), and capital costs reaching $2.5 million per unit, resulting in only 18% adoption by large-scale manufacturers. Energy recovery inefficiencies and product matrix variations (e.g., lipid-protective effects in emulsified meats) further exacerbate these challenges. Emerging solutions include semi-continuous systems (35% throughput increase), pulsed HPP protocols (18% energy reduction), and solar-hybrid installations (40% emission cuts), though economic viability remains problematic. We conclude that while HPP offers unparalleled safety and quality benefits, its scalability and energy intensity require coordinated innovations in process engineering, renewable energy integration, and cooperative industry models to achieve sustainable implementation.